Changes in biochemical profile after endotoxic shock - GREWAL, JASDEEP SINGH; SODHI, S P S; SINGH, DIGVIJAY (The Indian Journal of Animal Sciences, 2013)
Male buffalos calves (8) between 8 and 10 months of age after jugular catheterization were given Escherichia coli endotoxm @ 0.6 mglkg body weight mtravenously. Effect of endotoxin was studied at 0,5, 15,30,60 and 120 min. Acid phosphatase and GOT. enzymes in blood plasma increased whereas level of alkaline phosphatase decreased. The concentration of histamine in blood increased significantly after the effect of endotoxic shock in buffalo calves.